Effect of Air Distributor Types and Distribution Techniques on Fluidized Bed Drying of Sunflower Seeds - Phairoach Chunkaew (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objectives of this research were to investigate the effect of distributor types on the hydrodynamic behavior of a fluidized bed containing sunflower seeds for selecting an optimal distributor plate, to investigate operating parameters effecting on drying kinetics and salted sunflower seed quality utilizing a fluidized bed, to develop the drying kinetics models and to investigate the effect of distribution techniques in fluidized bed on the drying performance for salted sunflower seed.